Corporate Decisions: Innovations of the Russian Law and Practice - ALLANINA, Lilija M.; KHAIRULLINA, Nursafa G.; KONOVA, Tatjana A.; ZYKOVA, Vera K.; LOBODENKO, Elena I. (Journal of Advanced Research in Law and Economics; Vol 7 No 2 (2016): JARLE, Volume VII, Issue 2(16), Spring 2016, 2016)
The research deals with the problems of proper identification and registration of decisions made by the general meeting of corporation. This is due to the introduction in the Russian civil law of the new rules of management and control in business entities. Since the new system of identification methods of enterprise decisions has caused a large number of difficulties in implementation, the author analyzes the legal rules dedicated to notarization of decisions of general meeting of business entities, and especially the judicial practice (interpretation of the relevant rules of the Russian courts of law). The study questions the need for notarization of corporate decisions, which set another, in addition to notarization, way of confirming the decision, as well as issues of proliferation of new rules on business entities, consisting of one (single) member (shareholder). The authors also address controversial questions about the legal nature of enterprise decisions.